The Effect of Etpt Diet Therapy on Body Weight, Energy Intake, and Macronutrition in Malnutritional Schizophrenia Patients - Alfy Daniyati Rohmah; Anugrah Novianti; Mertien Sa’pang; Khairizka Citra Palupi; Putri Ronitawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Schizophrenia is associated with many health problems because changes in body weight will increase morbidity and mortality. Schizophrenic patients who come from social services have an average nutritional status of underweight and very thin (poor) categories. Purpose : This study aims to knowing the effect of giving ETPT diet therapy on changes in body weight, energy intake, and macronutrients in malnourished schizophrenic patients. Methods: This type of research was quasi-experimental research with a one group pretest-posttest design, using simple random sampling technique, namely 50 subject. Data were obtained from patients with malnutrition status who received the ETPT diet from the third classa adult inpatient ward. Data analysis in this study used paired t-test for changes in body weight and Wilcoxon test for energy intake and macronutrients. Results: This study showed there were significant differences in the changes in the respondents' weight while being given the ETPT diet. The difference in the average change in the respondent's weight during the 14 days of treatment was 2.18 kg. There was a change in energy intake on the first 7 days the patient was admitted, but there was no change in energy on the second 7 days the patient was treated. However, there is an increase in the average energy intake, which is not too much but already fulfills his needs. The average difference in changes in energy intake is 40.3 kcal. Overall energy intake in 14 days of treatment with P-Value = 0.055 (P-Value > 0.05), which means there is no change in energy intake. There were changes in protein, fat, and carbohydrate intake during treatment with an average difference in changes in protein intake of 2.7 grams, 2.0 grams of fat, and 14 grams of carbohydrates, with a P-Value = 0.000 (P-Value<0.05). Conclusions: There is an effect of giving ETPT diet therapy on body weight, energy intake, andmacronutrients in malnourished schizophrenic patients before and after intervention at the Mental Hospital Dr. Soeharto Heerdjan Jakarta.